Decoding the switch the functions of code switching in the classroom - Metila, Romylyn A. (2009)
This study identified the functions of codeswitching in the interactions of a fourth year class in a private girls' school. The non-participant observation method was used to document classes and break periods. Gathering of perceptions regarding codeswitching was done by conducting a survey among students and by interviewing teachers. The functions of codeswitching utterances were identified by analyzing the conversational context in which they occur. The results showed that codeswitching functions spanned pedagogical, communicative, social, and psychological aspects. Forty-four percent of the 34 student respondents viewed codeswitching as natural and acceptable, while 50 percent did not; four out of five teachers did not favor codeswitching, and three allowed its conditional use in the classroom. The pedagogical and communicative functions of classroom codeswitching justify its use in teaching and learning contexts, but it is recommended that codeswitching be restricted to informal classroom activities.
Keywords: Bilingualism; Codeswitching; Semilingualism